Evaluation of the antibacterial and physical properties of glass ionomer cements containing chlorhexidine and cetrimide: An in-vitro study - Deepalakshmi Mohanavelu; Poorni Saravanan; Miglani Revathi; Rajamani Indira; Ramachandran S (Wolters Kluwer Medknow Publications, 2010)
Background: Incorporation of antibacterial agents frequently results in changes in the physical properties of restorative materials. Materials and Methods: This in-vitro study investigated the antibacterial and physical properties of Glass ionomer cement (GIC) with chlorhexidine and cetrimide, to determine the optimal concentration, for incorporation of these agents to obtain antibacterial GICs for use with the Atraumatic restorative treatment approach. This was assessed using the agar diffusion test. Chlorhexidine diacetate and cetrimide were added to Glass ionomer cement type-IX (GIC-FUJI IX) at 1 and 2% W/W ratio. The experimental GIC specimens were placed on agar plates inoculated with Lactobacillus casei, and the area of inhibition was calculated after 48 hours. Results: All the experimental GICs exhibited inhibition of bacteria, but the sizes were dependent on the concentration of the antibacterial agent. Incorporation of chlorhexidine diacetate and cetrimide, at 2%, significantly decreased the compressive strength, and the setting time was extended a little by the addition of any concentration of chlorhexidine and cetrimide. Conclusions: The present study demonstrated that experimental GICs containing chlorhexidine diacetate and cetrimide were effective in inhibiting bacteria associated with caries, and incorporation of 1% cetrimide was optimal to give the appropriate antibacterial and physical properties.